2012
DOI: 10.1007/s12020-012-9668-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple once-daily subcutaneous doses of pasireotide were well tolerated in healthy male volunteers: a randomized, double-blind, placebo-controlled, cross-over, Phase I study

Abstract: A randomized, double-blind, placebo-controlled, cross-over, dose-escalating, single-center study was conducted to evaluate the safety, tolerability, and pharmacokinetic (PK) profile of multiple once-daily (qd) subcutaneous (sc) doses of pasireotide in healthy male subjects. Subjects received pasireotide 50, 200, or 600 μg sc qd for 14 days and placebo in separate sequences. Thirty-three subjects were randomized. The most frequently reported drug-related adverse events were injection-site reactions (n = 18), di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The primary objective of the study was to evaluate the effect of pasireotide on the baseline‐ and placebo‐corrected QTcI and was not specifically designed to evaluate the safety of pasireotide treatment. Nevertheless, these findings are consistent with results from other Phase I studies conducted in healthy volunteers, in which pasireotide demonstrated good tolerability at single doses up to 1,500 µg or with daily infusion up to 2,050 µg for 7 days, with the most common treatment‐related AEs being gastrointestinal …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The primary objective of the study was to evaluate the effect of pasireotide on the baseline‐ and placebo‐corrected QTcI and was not specifically designed to evaluate the safety of pasireotide treatment. Nevertheless, these findings are consistent with results from other Phase I studies conducted in healthy volunteers, in which pasireotide demonstrated good tolerability at single doses up to 1,500 µg or with daily infusion up to 2,050 µg for 7 days, with the most common treatment‐related AEs being gastrointestinal …”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, these findings are consistent with results from other Phase I studies conducted in healthy volunteers, in which pasireotide demonstrated good tolerability at single doses up to 1,500 mg or with daily infusion up to 2,050 mg for 7 days, with the most common treatment-related AEs being gastrointestinal. [29][30][31][32][33] Although early studies have indicated that somatostatin analogues may prolong QT interval, a direct comparison between the effects of pasireotide and other somatostatin analogues is not possible as there are no ICH E14compliant TQT studies published on these other agents. 13 A recent Phase III pasireotide study in patients with Cushing's disease reported treatment-emergent QTcF prolongation of >480 milliseconds in only 3/162 (2%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 For pasireotide SC, the AUC contribution of the terminal phase to AUC inf was minimal, and has been reported in the range of 7% to 15%, 10,12 with an effective half-life of approximately 12 hours. 8,9 A washout period until day 14 was allowed after the pasireotide PK sampling to ensure the complete elimination of pasireotide, and was considered sufficient because it represented more than five effective half-lives of pasireotide SC. 9,17 Following the washout period, verapamil (verapamil IR 120 mg two tablets once daily with 200 mL noncarbonated water in a fasting state for the IR cohort or verapamil SR 240 mg once daily~30 minutes after breakfast for the SR cohort) was administered to the subjects for 10 days (days [15][16][17][18][19][20][21][22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…In patients with Cushing's disease and acromegaly, pasireotide SC demonstrates a dose-proportional and time-independent pharmacokinetic (PK) profile at a dose range of 300 to 1200 mg. 5,[8][9][10][11] Pasireotide SC has shown a linear PK with acceptable safety and tolerability within a dose range from 2.5 to 1500 mg in healthy volunteers. 8 The PK profile of pasireotide SC in healthy volunteers exhibits rapid absorption (T max , 0.25-0.5 h), low clearance (CL/F,~8-9 L/h), large volume of distribution (V z /F >100 L), and effective half-life (T 1/2 eff ,~12 hours, based on area under curve [AUC] accumulation ratio with once-daily dosing for 14 days) with favorable tolerability in a single-or multiple-dose regimen.…”
mentioning
confidence: 99%
See 1 more Smart Citation